ESTIMASI BAYESIAN PARAMETER BUTIR TES DAN KEMAMPUAN PADA ITEM RESPONSE THEORY (IRT) MODEL 3-PL - MEMOLO, TUNDUNG ([Yogyakarta] : Universitas Gadjah Mada, 2015)
In this thesis, it will be discussed how to estimate parameters on Item Responses Theory (IRT). There are three models of logistics on IRT, One Parameter Logistics Model (1-PL), Two Parameter Logistics Model (2-PL), and Three Parameter Logistics Model (3-PL), the differences lay on how many parameter we used. Estimation method which issued on IRT in this thesis is Bayesian Estimation. Estimator of item characteristics, difficulty level (b), discrimination (a), and pseudo guessing (c), and estimator of examinee is examinee of ability () gain by using Numeric Method , Newton-Raphson Iteration. The characteristics of item are used to determined information function. The characteristics of examinee is used to choose items which high information function and adapted with ability in adaptive test.